Extracellular Fluid Excess Is Significantly Associated With Coronary Artery Calcification in Patients With Chronic Kidney Disease. Issue 13 (3rd July 2018) - Park, Seohyun; Lee, Chan Joo; Jhee, Jong Hyun; Yun, Hae‐Ryong; Kim, Hyoungnae; Jung, Su‐Young; Kee, Youn Kyung; Yoon, Chang‐Yun; Park, Jung Tak; Kim, Hyeon Chang; Han, Seung Hyeok; Kang, Shin‐Wook; et al.
Abstract : Background: Extracellular fluid (ECF) excess is an independent predictor of cardiovascular morbidity in patients undergoing dialysis. This study aimed to investigate the relationship between ECF status, which is affected by renal function, and coronary artery calcification (CAC), which is a marker of cardiovascular disease, in patients with chronic kidney disease (CKD). Methods and Results: A total of 1741 patients at all stages of pre‐dialysis CKD from the prospective observational cohort of CMERC‐HI (Cardiovascular and Metabolic Disease Etiology Research Center‐High Risk) were analyzed for the association between ECF status and CAC. ECF status was defined as extracellular water‐to‐total body water ratio (ECW/TBW) measured using bioelectrical impedance analysis. ECF excess was defined as ECW/TBW ≥0.390 or ≥0.400 depending on its severity. To define CAC, Agatston coronary artery calcium scores were measured. A total coronary artery calcium score of ≥400 was defined as CAC. The CKD stages were defined according to estimated glomerular filtration rate calculated using the CKD Epidemiology Collaboration equation. ECW/TBW and the proportion of ECF excess increased with progressing CKD stages. Multivariable logistic regression analyses showed that ECW/TBW was independently associated with CAC (per 0.01 increase of ECW/TBW, odds ratio 1.168, 95% confidence interval, 1.079–1.264, P <0.001). The adjusted R 2 for predicting higher coronary artery calcium scores and CAC significantly improved after ECW/TBW was added to conventional factors. This association was further confirmed by net reclassification and integrated discriminant improvements, sensitivity analysis, and subgroup analysis. Conclusions: ECF status is independently associated with a high risk of CAC in patients with CKD. Study Registration: URL: https://www.clinicaltrials.gov/ . Unique identifier: NCT02003781.